PENGARUH UKURAN KAP, UKURAN PERUSAHAAN KLIEN, SPESIALISASI AUDIT DAN FEE AUDIT TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021) - Sauh Hwee Teng; Yosefenny Samosir; Helen Helen; Wilen Wilen (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to analyze the effect of public accounting firms size, clients company size, audit specialization and audit fees on audit quality on food and beverage sub-sector manufacturing companies listed in Indonesia Stock Exchange in 2019-2021. The type of this study is quantitative using secondary data collected from financial statements and annual reports listed in the IDX. The population in this study is the food and beverage sub-sector manufacturing companies listed in Indonesia Stock Exchange in 2019-2021 total 39 companies and the sample in this study were 23 companies that had been selected with certain criteria. Data analysis techniques and hypothesis testing in this research used descriptive statistical analysis techniques and logistic regression analysis. The results of this study indicate that the public accounting firms size, clients company size, audit specialization and audit fees have no effect on audit quality in the food and beverage sub-sector manufacturing companies listed on the IDX for the 2019 2021 period. Keywords: Public Accounting Firms Size, Clients Company Size, Audit Specialization, Audit Fees, Audit Quality